Fiscal Implications of Trade Liberalization - Bevan, David (IMF Working Papers; Working Paper ;, 1995)
This paper examines the relationship between trade liberalization and the budget deficit, which depends on the specifics of country's economic structure, and the trade regime which is being liberalized. It relates some popular but incomplete approaches to assessing this issue (such as analysis of the foreign exchange budget) to a more comprehensive approach using an applied general equilibrium model. The argument is illustrated using data from the most recent of a sequence of abortive planned liberalizations in Kenya, as well as a number of stylized illustrations. The conclusions are not only that liberalization may be budget enhancing, but that in certain circumstances it may be strongly so.